Propuesta de Diseño de la Documentación del Sistema de Seguridad y Salud en el Trabajo en la Empresa Kreatica Mercadeo y Publicidad con base en la Norma ISO 45001: 2018 (2023)
For organizations, having the SGSST design represents the continuous improvement and protection of their workers, it is one of the main procedures that the company must carry out, additionally for clients it is a way of projecting an excellent image and high credibility , as there are no incidents and provide employees with a healthy and protected environment, which would not affect delivery times, much less stop the production or delivery of their products. Kreatica Marketing and Publicity is a leading company in the advertising sector, it could not be the exception in ensuring the protection of its collaborators, for this reason it requires the design of the SGSST, for its subsequent implementation; Not only will compliance with system requirements help prevent accidents at work, but it will also avoid fines for non-compliance with legal matters on safety and health at work. For this reason, in the present work, a methodology was developed starting with the diagnosis through the checklist that for this case corresponded to the ISO 45001:2018 Standard, in order to verify compliance with the requirements, subsequently and having as Based on the design of similar documentation for other organizations, some formats were taken and adjusted according to the characteristics of the company Kreatica Marketing and Advertising. And as a final part, the viability of the design of the SGSST documentation was evaluated as viable from the economic point of view. Keywords: ISO, Management system, Occupational Health and Safety, Regulations, Format.